PENGELOLAAN ROYALTI MUSIK DAN LAGU DI PLATFORM YOUTUBE - Imansah, Rifai (JIPRO: Journal of Intellectual Property, 2022)
Copyright music and songs can be easily searched and listened to online through media such as youtube. This difficulty creates legal problems for music creators or musicians, namely the use of works without permission. This violates economic rights in the form of royalties for music and song creators. YouTube creators are facilitated when uploading music videos and songs in the youtube system, it provides an opportunity for creators to use creations that are not theirs. Youtube filters every uploaded video in its system. This study uses a legal and conceptual approach to determine the legal relationship and forms of protection for music creations and songwriters. The legal relationship of the parties that occurs on the youtube platform occurs through an agreement and creates rights and obligations between the parties. The protection provided by youtube is in the form of a license permit that must be made by the creator if you want to use someone else's copyright and must pay royalties to copyright holders through the Collective Management Institute.